2015
DOI: 10.1063/1.4906358
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasma wave assisted second harmonic generation of laser over a metal film

Abstract: Second harmonic generation of laser mode converted surface plasma wave (SPW) over a corrugated metal film is studied. The laser, impinged on the metal film, under attenuated total reflection configuration, excites SPW over the metal-vacuum interface. The excited SPW extends over a much wider surface area than the laser spot cross-section. It exerts a second harmonic ponderomotive force on metal electrons, imparting them velocity that beats with the surface ripple to produce a nonlinear current, driving resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A thin metal layer over a glass prism with a thin layer of semiconductor over it has been considered in Kretschmann ATR configuration as shown in Fig. 1, where, laser light is incident at an acute angle on metal glass interface leading to SPW in metal [16]. The em fields of laser interact with electrons of metal and produce SPW of nearly the same frequency as laser but with higher amplitude.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A thin metal layer over a glass prism with a thin layer of semiconductor over it has been considered in Kretschmann ATR configuration as shown in Fig. 1, where, laser light is incident at an acute angle on metal glass interface leading to SPW in metal [16]. The em fields of laser interact with electrons of metal and produce SPW of nearly the same frequency as laser but with higher amplitude.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…with m  and s  as the permittivity of metal and semiconductor respectively and s  is the frequency of surface plasma wave. The frequency of SPW is nearly same as the frequency of the laser, so    s [16]. Amplitude of surface plasma wave s A depends on amplitude of incident laser A with  .…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Chauhan and Parashar. [10] theoretically studied second harmonic generation assisted by SPW over a metalvacuum interface using Kretschmann attenuated total reflection (ATR) configuration and their work showed that the presence of external factors like grating structure or density ripple helps to enhance the harmonic generation efficiency. Sharma et.al.…”
Section: Introductionmentioning
confidence: 99%
“…In modern times, several schemes have been provided by research workers for the generation of second harmonics with the use of various techniques, such as planar optical waveguides, selfsustained plasma channels, density modulated plasma, accelerator-based sources, optical rectification, sources based on laser-cluster interaction, SHG using CNTs [1][2][3][4][5][6]. SHG is a nonlinear optical phenomenon that arises in the laser-matter interaction in which photons with some frequencies interacting with the nonlinear material are effectively combined to produce new photons with twice the frequency and energy.…”
Section: Introductionmentioning
confidence: 99%